Shifting from Conventional to Islamic Banking: Challenges and Barriers (a case study on Libya) - Abdelrahman M. Abudirbala , Mohamed M. Mukhtar (Journal of Pure & Applied Sciences, 2019)
Since the beginning of the 21st century, there have been a few steps towards the implementation of Islamic banking in the state. Nevertheless, in addition to the overall lack of research considering issues of Islamic banking in Libya, there has been no clear and practical path for banks transforming to an Islamic banking model. The purpose of this study is to identify the barriers and challenges that facing banks to converting into Islamic banking in Libya. In order to answer this question, a quantitative approach is followed. Questionnaires were adopted to collect data from staff of five Libyan banks namely Jumhouria bank, AL Waha Bank, Wahda bank, National Commercial Bank and North Africa Bank. The main obstacles that hinder the implementation of Islamic banking in Libya are a shortage of skills and experience which represented in the distinct lack of human capital trained for Islamic banking, and a lack of awareness which is represented in the absence of education and training institutions that provide the new entities with the required staff, and infrastructure issues which are represented in weakness in technical accounting system.